PRIORITIES OF HIGhER EDUCATION IN POLAND AND IN EUROPE - Kaminska, Malgozhata (The Modern Higher Education Review, 2017)
The article presents an analysis of the most important priorities for higher education in Poland and in Europe. The main objectives and tasks are outlined on the basis of the selected strategic documents, reports and statements of various Polish and international bodies interested in education at a higher level. Challenges for higher education in Poland and Europe relate to different dimensions. First of all, issues related to the quality of education and its accessibility, organizing the education process and financing, as well as research and development activities in national and international scale come to the fore. An important priority is connecting of learning outcomes with the labour market. These challenges arise from the plan to build an economy based on knowledge and innovation, as well as continuing the concept of learning throughout life.